Effectiveness of Business Dispute Resolution Through Arbitration in Indonesia - Rian Sukmawan, Bennadi, Samsul Arifin (JURIDISCH DENKEN, 2026)
This article analyzes the effectiveness of arbitration in resolving business disputes in Indonesia. The study employs normative juridical research by examining statutory regulations, doctrinal perspectives, institutional practice, and enforcement mechanisms. The research evaluates arbitration based on legal certainty, procedural efficiency, enforceability, accessibility, and institutional legitimacy. The findings show that arbitration provides confidentiality, expertise-based adjudication, flexibility, and final binding decisions that support commercial stability. However, structural constraints such as cost, regional access limitations, and enforcement formalities remain significant. The article concludes that arbitration is substantively effective but requires regulatory refinement and institutional strengthening